POSSIBILITY OF DISTRIBUTION THE EXOSOMES DERIVED FROM MULTIPOTENT STROMAL CELLS TO THE MYOCARDIUM AFTER INJECTION INTO THE BONE TISSUE OF A LIMB - Кузькин, Сергей Александрович; Майбородин, Игорь Валентинович; Шевела, Александр Андреевич; Майбородина, Виталина Игоревна; Лушникова, Елена Леонидовна; Шевела, Андрей Иванович (Medicine in Kuzbass, 2021)
Objective: The aim of the investigation was to establish the possibility of migration into the heart of EMSCs labeled with a fluorescent dye after their introduction into an artificially created defect in the bone tissue of a limb in an experiment.Methods. Bone injury was modeled by creating standardized holes 4 mm deep in the proximal tibial condyles of rabbits with a dental bur with a diameter of 2 mm. 27 animals were injected with a warm saline solution in phosphate buffer with an insulin syringe into a bone tissue defect on the right and left extremities; 30 animals received 19.5 μg of EMSCs in the same buffer into similar defects on each limb. Multipotent stromal cells were obtained from the bone marrow of Wag male inbred rats. EMSCs was stained with PKH26 fluorescent dye.Results. Three days after the operation, single objects were found in the myocardium of the animals, which glowed very brightly when the rhodamine filter was installed. The size of the objects fluorescent in red never exceeded 1 μm, most often they were much smaller, that is, they were dusty. Luminous particles were most often located near vessels, in their walls or on the endothelium of capillaries. By the 7th day, brightly luminous objects have almost completely disappeared from the myocardium. After 10 days in the heart muscle, weakly fluorescent red objects were detected extremely rarely. EMSCs adsorption by any cells was not detected.Field of application. Regenerative medidcine.Conclusions. The detection on the 3rd and 7th days in the myocardium of even single EMSCs after their introduction into the defect of the hind limb bone indicates that their penetration into the vascular bed with subsequent migration into the myocardium is possible.
Keywords: multipotent stromal cell exosomes; exosome distribution; bone tissue defect of a limb; heart; fluorescence microscopy